2016
DOI: 10.1080/21501203.2016.1218966
|View full text |Cite
|
Sign up to set email alerts
|

Differential methods of localisation of fungal endophytes in the seagrasses

Abstract: Sections of three seagrass species (Halophila ovalis, Cymodocea serrulata and Halodule pinifolia) were assessed for endophytes based on differential staining using light and fluorescence microscopy method. Acridine orange and aniline blue detected endophytic fungi in 20% and 10% of the segments, respectively, whereas lactophenol cotton blue was more sensitive to detect the fungal hyphae in 70% of the segments. Hyphae were the principal fungal structures generally observed under the cuticle, within the epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…The penetration of fungal hyphae to neighboring cells through the cell wall indicated carbohydrate enzymatic digestion. However, some ndings of our study were different from the report of Raja et al (2016). For instance, fungal hyphae colonized the neighboring cells even a single cell was not yet completely lled up.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The penetration of fungal hyphae to neighboring cells through the cell wall indicated carbohydrate enzymatic digestion. However, some ndings of our study were different from the report of Raja et al (2016). For instance, fungal hyphae colonized the neighboring cells even a single cell was not yet completely lled up.…”
Section: Discussioncontrasting
confidence: 99%
“…Endophytic colonization in both intercellular and intracellular spaces in the leaves were also reported in C. serrulata, T. hemprichii and Halophila ovalis indicating endophytes' close interaction with their hosts (Raja et al 2016). The penetration of fungal hyphae to neighboring cells through the cell wall indicated carbohydrate enzymatic digestion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The high larval mortality and sporulation rates observed in foliar applications can be explained by the high number of fungal conidia that must have been in direct contact with the cuticle of the larvae and hence germinated and invaded their haemocoel, thereby inducing mycosis (Butt et al, 2016). In the endophytic colonization treatments, however, we assumed that B. bassiana was translocated systemically through the plant tissues (Raja et al, 2016) and that larval infection occurred through ingestion of its hyphae in the palisade parenchyma of cabbage leaf tissues (Heviefo et al, 2017), with no direct exposure to conidia. Subsequently, the ingested ramified hyphae would have developed in the haemocoel of the infected larvae thereafter producing spores and toxins (Ownley et al, 2010) that induced lower levels of mortality and sporulation compared with the foliar applications, as also reported by Butt et al (2016) and(Ortiz-Urquiza et al, 2010) and could explain why we only observed 57.61 ± 2.15% corrected larval mortality rate in the endophytic treatment (Endo 3) instead of 100% mortality induced by foliar application, as also reported by Butt et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…A21 was subsequently inoculated in rice roots for 15 days under the above culture conditions. The fungal dye, aniline blue [43] was utilized to dye A21 in the rice roots. The submicroscopic structures of A21 in roots were observed using the same SEM method described above.…”
Section: Co-culture and Stainingmentioning
confidence: 99%